2006
DOI: 10.1530/eje.1.02257
|View full text |Cite
|
Sign up to set email alerts
|

A perspective view of sodium iodide symporter research and its clinical implications

Abstract: The sodium iodide symporter (NIS) is an intrinsic plasma membrane protein that mediates active iodide transport into the thyroid gland and into several extrathyroidal tissues, in particular the lactating mammary gland. Cloning and molecular characterization of the NIS have allowed the investigation of its key role in thyroid physiology as well as its potential pathophysiological and therapeutic implications in benign and malignant thyroid diseases. Similarly, elucidating the mechanisms underlying the regulatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
117
1
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 167 publications
(120 citation statements)
references
References 143 publications
1
117
1
1
Order By: Relevance
“…9 Another application is the combination of the imaging and therapeutic potential of the hNIS transgene. 35 Oncolytic recombinant measles viruses encoding hNIS have already been described 36,37 and used to demonstrate the concept of image-guided radiovirotherapy in a pre-clinical model of multiple myeloma. 36 Our work suggests the possibility to extend this concept to adenoviruses.…”
Section: Spect/ct Imaging Of Oncolytic Adenovirusesmentioning
confidence: 99%
“…9 Another application is the combination of the imaging and therapeutic potential of the hNIS transgene. 35 Oncolytic recombinant measles viruses encoding hNIS have already been described 36,37 and used to demonstrate the concept of image-guided radiovirotherapy in a pre-clinical model of multiple myeloma. 36 Our work suggests the possibility to extend this concept to adenoviruses.…”
Section: Spect/ct Imaging Of Oncolytic Adenovirusesmentioning
confidence: 99%
“…This can be correlated with data in the human PTC. It could be due to an increased intracellular NIS misexpression (Saito et al, 1998;Wapnir et al, 2003;Riesco-Eizaguirre and Santisteban, 2006), to conformational changes (Gérard et al, 2003) or to the non maturation of hNIS (Trouttet-Masson et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Delivery of exogenous hNIS in vitro resulted in more than a 120-fold increase in iodide uptake in U1240 cells infected with recombinant adenovirus expressing hNIS regulated by the CMV promoter. Intratumoural injection of Ad-CMV-hNIS into subcutaneous xenografts of U251 human gliomas resulted in a 25-fold increase in 125 I accumulation compared to the spleen or saline-injected tumours [134]. Mandell et al (1999) demonstrated in vitro and in vivo iodide accumulation in melanoma, liver, colon and ovarian carcinoma cells after retrovirus-mediated transfection with rNIS.…”
Section: Preclinical Studies Of Nis Gene Transfer By Replication-defementioning
confidence: 99%
“…Rats fed on T4-supplemented diet did not show any uptake in the thyroid on subsequent 99m TcO 4 − scintigraphy. Furthermore, this correlated with a reduced level of NIS protein expression on western blot analysis [134]. Most subsequent studies have employed low-iodine diets combined with T4 supplementation (0.05-5 mg/l) for 1-2 weeks prior to radioiodide therapy [128,[150][151][152][153].…”
Section: Thyroid Gland Suppression As a Strategy During Nis Gene Therapymentioning
confidence: 99%